Learning Satisfaction as a Mediator of the Influence of Teachers' Digital Competence and Blended Learning on Student Academic Achievement in Junior High Schools in Rangkasbitung District, Banten Province - Siti Muzdalifah (Journal of Education and Teaching Learning, 2026)
This study aims to examine the direct and indirect effects of teachers' digital competence and blended learning on student academic achievement, mediated by learning satisfaction, in junior high schools within regions experiencing technological infrastructure disparities. Methodology: A quantitative associative approach with a cross-sectional design was employed. Participants comprised 143 teachers and 143 eighth-grade students from six public junior high schools in Rangkasbitung Sub-district, Lebak Regency, Banten Province, selected using proportionate stratified random sampling based on Slovin's formula. Data were gathered through a Likert-scale questionnaire triangulated with academic report card records, and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 3. Results: All eighty indicators were declared valid and reliable. Teachers' digital competence and blended learning both exerted significant positive effects on student learning satisfaction and academic achievement. Furthermore, learning satisfaction was proven to act as a partial mediator in both causal pathways. The structural model accounted for 66.8% of the variance in learning satisfaction and 71.2% of the variance in student academic achievement. Conclusion: Student academic achievement is determined more through the indirect enhancement of learning satisfaction than by the direct influence of teachers' digital competence or blended learning alone. Thus, learning satisfaction serves as a vital linking mechanism within the hybrid learning ecosystem at the junior high school level. Limitations: This study utilized a cross-sectional design, relied partially on self-reported data, and was restricted to six schools within a single sub-district; hence, generalizability to other contexts should be made with caution. Contribution: These findings provide valuable insights for local educational policymakers, school principals, and teachers in designing professional development and blended learning programs aimed at reinforcing student learning satisfaction. Additionally, it enriches the literature on digital education within the context of developing regions facing infrastructure constraints.